HOW A RIDGE-FURROW RAINWATER HARVESTING SYSTEM WITH PLASTIC FILM-MULCHED RIDGES AFFECTS RUNOFF GENERATION, RAINFALL STORAGE, AND WATER MOVEMENT IN SEMI-ARID REGIONS IN CHINA - Qu Yang; Gao Xiaoli; Feng Baili (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
Ridge-furrow rainwater harvesting with alternate white plastic film-mulching has been shown to be an easy and efficient method to harvest rainwater and improve crop yield in arid and semi-arid regions in China. To explore how this system affects the pattern of water movement, the water content of the soil, and runoff generation, two systems were designed and tested in Fugu, Yulin, Shaanxi, China from 2010 to 2012. There were three treatment groups as follows: a flat control plot with no mulching (NM), a plot with furrow and ridge widths of 60 cm (P60), and a plot with furrow and W-shaped ridge widths of 40 cm (W80). W80 was found to have a higher mean rate of runoff generation than P60 (83.1% and 70.3%, respectively). Additionally, compared with the other groups, W80 exhibited increased rainwater storage beneath the furrow in both rainy and dry seasons. The water content of the soil beneath the ridges of all treatment groups was higher after rainfall than before rainfall, and the rainwater infiltration rate was higher at 24 h after rainfall than at 48 h after rainfall. Moreover, the water content of the soil under the ridge was higher at the pre-measured stage than at the later measured stage, suggesting that it is not effective for short-term rainfall. Yield, water use efficiency, and soil water storage of rainwater harvesting practices had more advantage than that of NM. These findings suggest that using a ridge-furrow rainwater harvesting system with alternate plastic film-mulching can improve runoff generation, increase rainwater storage, and decrease water loss from the soil. In this system, the water from the soil moved from planted furrows to ridges during rainfall, but the water moved from ridges to planted furrows in the dry season. The W80 system with the W-shaped ridge performed better than the other groups with respect to rainwater storage, evaporation control, runoff generation, and water use efficiency.